2016
DOI: 10.1111/bpa.12456
|View full text |Cite
|
Sign up to set email alerts
|

Microglia show altered morphology and reduced arborization in human brain during aging and Alzheimer's disease

Abstract: Changes in microglia function are involved in Alzheimer's disease (AD) for which ageing is the major risk factor. We evaluated microglial cell process morphologies and their gray matter coverage (arborized area) during ageing and in the presence and absence of AD pathology in autopsied human neocortex. Microglial cell processes were reduced in length, showed less branching and reduced arborized area with aging (case range 52-98 years). This occurred during normal ageing and without microglia dystrophy or chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(156 citation statements)
references
References 46 publications
(79 reference statements)
13
143
0
Order By: Relevance
“…Interestingly, it has been described that dystrophic or senescent microglia might undergo age-dependent degeneration and are believed to lose their neuroprotective functions, thereby, contributing to the age-dependent onset of sporadic AD (sAD; Streit et al, 2009). Altered microglia morphology and reduced arborization have been reported in the human brain during aging and in AD patients (Davies et al, 2016). It remains unclear whether the observed morphological changes are signs of microglia degeneration and a recent study suggests that the reported microglia dystrophy might reflect age-related cytoskeleton alterations (Tischer et al, 2016).…”
Section: Aging Microglia: Priming Functions and Phenotypesmentioning
confidence: 99%
“…Interestingly, it has been described that dystrophic or senescent microglia might undergo age-dependent degeneration and are believed to lose their neuroprotective functions, thereby, contributing to the age-dependent onset of sporadic AD (sAD; Streit et al, 2009). Altered microglia morphology and reduced arborization have been reported in the human brain during aging and in AD patients (Davies et al, 2016). It remains unclear whether the observed morphological changes are signs of microglia degeneration and a recent study suggests that the reported microglia dystrophy might reflect age-related cytoskeleton alterations (Tischer et al, 2016).…”
Section: Aging Microglia: Priming Functions and Phenotypesmentioning
confidence: 99%
“…>80 years old). More recently, shortening of microglial cell processes and reduced of coverage of brain parenchyma with normal ageing and AD has been reported .…”
Section: Introductionmentioning
confidence: 98%
“…In this regard, it has also been hypothesized that aging leads to the dysfunction or dystrophia of these cells (34). Nevertheless, a larger reduction in process length and arborized area in AD compared to aged-matched control microglia has recently been described (41).…”
Section: Microgliamentioning
confidence: 99%